The Aspirations of Measurement for Change - Krapels, Joachim; van der Haar, Lotte; Slemming, Wiedaad; de Laat, Joost; Radner, James; Sanou, Anselme Simeon; Holding, Penny (Frontiers in Public Health, 2020)
This Perspective presents the five key aspirations of an approach to data use, decision making and monitoring, evaluation, and learning (MEL) in Early Childhood Development (ECD) referred to as Measurement for Change. The core ideas of Measurement for Change gave rise to this series, and many of the papers submitted in this series speak to this approach, whether directly or indirectly. The five aspirations describe interconnected concepts that advocate for practitioners and researchers within ECD to build the capacity to use data in their decision making, by establishing a monitoring, evaluation, and learning system that strives to be: Dynamic; Inclusive; Informative; Interactive; and People-centered.